Pouring from an Empty Cup: The Case for Compassion Fatigue in Higher Education - Cordaro, Millie (Building Healthy Academic Communities Journal, 2020)
Background: With the global pandemic, higher education has experienced unparalleled changes with abrupt transitions to remote and online learning. Faculty are working to provide continuity of teaching and support to students whose lives have been disrupted; therefore, faculty are finding themselves managing distressed students with a wide range of issues, while also managing their own intrapersonal stress. Consequently, faculty may experience feelings of being psychologically overwhelmed and emotionally exhausted. Aim: This article informs faculty in higher education on the concept of compassion fatigue along with the symptoms, warning signs, and risk factors. In addition, protective factors, including self-care plans and coping strategies are addressed. Methods: A comprehensive review of the literature on compassion fatigue was conducted including the application of the construct to teaching and education. The literature review illuminates the use of compassion fatigue, originating from the scientific disciplines of counseling and traumatology, within an emerging line of research findings occurring amongst educators prior to the COVID-19 pandemic. Results: The literature demonstrates that compassion fatigue as a prospective, intrapersonal condition may potentially affect some faculty in higher education, and the proposed conceptual application of the construct to teaching and education can assist with acknowledging and understanding an important aspect of faculty mental health. Conclusions: Given the crisis surrounding the pandemic, it's essential for faculty to be aware of compassion fatigue in order to mitigate potential intrapersonal psychological and emotional consequences. Elucidating the symptoms and implications of compassion fatigue for faculty in higher education is part of a broader, overlooked issue on faculty mental health and wellness.